PENGGUNAAN MEDIA SPINNER UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA MATERI KALIMAT AKTIF DAN PASIF PADA PESERTA DIDIK KELAS II SDI WAHID HASYIM SIDOARJO - Familia, Cindy; Wardono, Mohammad Setyo (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2023)
The aim of this research is to determine the improvement in learning outcomes in Indonesian, the difference between active and passive sentences using spinner media. This research uses classroom action research (PTK) carried out in several cycles. Each cycle consists of 4 stages, namely planning, implementation, observation and reflection.. The results of the research show that Indonesian language learning activities using Spinner media have increased. This is shown by an increase in the percentage of teacher activity in cycle I reaching 63.15% and cycle II reaching 89.50%. Student activity during Indonesian language learning activities using Spinner learning media has increased. This is shown by an increase in the percentage of student activity in cycle I reaching 67.4% and cycle II reaching 88.22%. Increased student learning outcomes after participating in Indonesian language learning activities using Spinner learning media. This can be shown by an increase in the percentage of learning outcomes for students in cycle I reaching 72.6% and cycle II reaching 90.13%.